Neutron Spin Rotation at Laue Diffraction in a Weakly Deformed Transparent Crystal with No Center of Symmetry - Voronin, V. V.; Fedorov, V. V.; Semenikhin, S. Yu; Kuznetsov, I. A.; Berdnikov, Ya. A. (Journal of experimental and theoretical physics, 2019)
The effect of neutron spin rotation at Laue diffraction in a weakly deformed neutron-transparent noncentrosymmetric crystal has been described theoretically and studied experimentally. The effect is due to the bending of a Kato trajectory of the neutron in the deformed crystal. At a certain type of deformation, one of two neutron waves excited at Laue diffraction, which propagate in opposite crystal fields in the crystal with no center of symmetry, leaves the crystal. As a result, the spin of the remaining neutron wave is rotated by a certain angle with respect to initial direction due to the interaction of the magnetic moment of a moving neutron with the crystalline electric field. This effect is absent in an undeformed perfect crystal, where only the depolarization of a beam occurs because both waves in opposite electric fields have the same amplitude. A method has been developed for controlled deforming the perfect single crystal by creating a temperature gradient in it. Thereby, a new possibility of measuring electric fields acting on a neutron in noncentrosymmetric crystals, as well as a method of controlling these fields in experiments on studying the fundamental properties of the neutron, has been implemented.